Madhjamaka Nagardżuny : filozofia czy terapia? - Jakubczak, Krzysztof (2021)
NĀGĀRJUNA’S MADHYAMAKA: PHILOSOPHY OR THERAPY? Nāgārjuna was a Buddhist philosopher living in India, in the second century Ce. He gave rise to a philosophical school known later as Madhyamaka or the Middle Way School. My aim in this work was to give a reader the foundations for critical attitude towards multiplicity of opinions about nāgārjuna’s philosophy and, on the other hand, to elucidate a few questions which are notoriously presented in a vague way.The first aim I carry when discussing the issue of an appropriate research method. The method to study nāgārjuna’s philosophy I propose is an eclectic one. Different cognitive perspectives are combined in it and treated as complementary rather than mu-tually excluding. To accomplish my second objective I consider the question of dialecti-cal nature of Madhyamaka, the narrative structure of nāgārjuna’s texts, the function of tetralemma, and the theory of language, including linguistic realism, meaning, and reference, and also the conception of emptiness, or the way things are.